PERGESERAN POLITIK HUKUM KOPERASI DALAM UU RI NO. 25 TAHUN 1992 DAN UU RI NO. 17 TAHUN 2012 SERTA PUTUSAN MAHKAMAH KONSTITUSI NO. 28/PUU RI -XI/2013 - Tri Budiyono; Christina Maya Indah S (Faculty of Law, Universitas Diponegoro, 2015)
This research revealed the shift of political law as a result of implementation Act of Republic of Indonesia No.17 of 2012 that reposition Act of Republic of Indonesia No.25of 1992. The implementation of Act of Republic of Indonesia No.17 of 2012 leaved crusial problem because of the lack of values ethic of cooperative. The crucial problems in Act of Republic of Indonesia No.17of 2012 related with the reduce of cooperative concept by limited as a legal entity. Beside that, the capital aspect has potential to reduce the value of cooperative, the appointment of cooperative management of non members, and the power of supervisory board of cooperatice, and the distribution of surplus operating results . The constitutional court with erga omnes character canceled act of Republic of Indonesia No.17 of 2012 and maked transtitional to re implement Act of Republic of Indonesia No 25 of 1992 as a focus in this research.